Introducing Svalbard Studies - Chekin, Leonid S.; Rogatchevski, Andrei (Nordlit, 2020)
Svalbard, or “cool edge” in Old Norse, is an archipelago in the Arctic Ocean. It has no indigenous population and some 60% of its landmass is covered by ice. Yet its rich wildlife and mineral resources, as well as spectacular sights, have been attracting a great deal of commercial interest ever since Willem Barentsz discovered the archipelago in 1596 and named it Spitsbergen (“peaked mountains”). Initially a whale hunting base and subsequently a mining ground, a tourist destination and an Arctic research centre, Svalbard could have belonged, among others, to the Dutch, the British and the Russians (who claim to have visited it before Barentsz) – but ended up under Norwegian jurisdiction, upon an international approval of the so-called Svalbard Treaty.